1998
DOI: 10.1128/iai.66.10.4867-4874.1998
|View full text |Cite
|
Sign up to set email alerts
|

Murine Dendritic Cells Pulsed In Vitro withToxoplasma gondiiAntigens Induce Protective Immunity In Vivo

Abstract: The activation of a predominant T-helper-cell subset plays a critical role in disease resolution. In the case of Toxoplasma gondii, the available evidence indicates that CD4+protective cells belong to the Th1 subset. The aim of this study was to determine whether T. gondii antigens (in T. gondii sonicate [TSo]) presented by splenic dendritic cells (DC) were able to induce a specific immune response in vivo and to protect CBA/J mice orally challenged with T. gondiicysts. CBA/J mice immunized with TSo-pulsed DC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(12 citation statements)
references
References 62 publications
0
10
0
2
Order By: Relevance
“…This reinforces the importance of DC in generating protective immune responses against infectious agents. Other groups have shown, for example, that similar strategies can be used to protect against experimental infections with Chlamydia trachomatis 14 and Toxoplasma gondii 15. Recently, BCG‐infected DC were shown to protect mice against an aerosol challenge with M. tuberculosis; 16 however, in these experiments the DC were given intratracheally a route which would favour local presentation to T cells but would not necessarily indicate systemic priming of naı¨ve T cells.…”
Section: Discussionmentioning
confidence: 99%
“…This reinforces the importance of DC in generating protective immune responses against infectious agents. Other groups have shown, for example, that similar strategies can be used to protect against experimental infections with Chlamydia trachomatis 14 and Toxoplasma gondii 15. Recently, BCG‐infected DC were shown to protect mice against an aerosol challenge with M. tuberculosis; 16 however, in these experiments the DC were given intratracheally a route which would favour local presentation to T cells but would not necessarily indicate systemic priming of naı¨ve T cells.…”
Section: Discussionmentioning
confidence: 99%
“…EVs derived from DC incubated with T. gondii antigens induce an intense immune response, increasing the levels of MHC class II and the specific production of T-cells and cytokines [ 140 ]. Studies of immunization with these DC are promising alternatives in promoting protection against T. gondii [ 141 , 142 ]. Eimeria tenella , Eimeria maxima , and Eimeria acervulina are also coccidian parasite of chickens that also release EVs, which confer protective immune response against the parasite [ 123 , 143 , 144 ].…”
Section: Parasite Vesiclesmentioning
confidence: 99%
“…It has been documented that following loading with pathogenic antigens and adoptive transfer, DCs mediate protection against a wide spectrum of infectious diseases, including toxoplasmosis. We previously showed that DCs pulsed with T. gondii antigen elicit protective immunity against chronic toxoplasmosis in mice ( 19 , 20 ). However, it is not feasible to use ex vivo antigen-loaded DCs for first-line prophylactic vaccination.…”
Section: Introductionmentioning
confidence: 99%